Trajectories of olfactory identification preceding incident mild cognitive impairment and dementia: a longitudinal studyResearch in context - Jie Guo; Abigail Dove; Jiao Wang; Erika J. Laukka; Ingrid Ekström; Michelle M. Dunk; David A. Bennett; Weili Xu (EBioMedicine, 2023)
Summary: Background: The pattern of olfactory identification change in the early phases of dementing disorders is unclear. We aimed to assess olfactory identification trajectories preceding incident mild cognitive impairment (MCI) and dementia and explore the role of brain pathologies in these trajectories. Methods: Within the Rush Memory and Aging Project, 1318 dementia-free older adults were followed annually for up to 11 years. Olfactory identification was assessed using the Brief Smell Identification Test annually. Of 900 cognitively intact participants, incident MCI and dementia were diagnosed following standard criteria. Over follow-up, 518 participants died and underwent brain autopsies for neuropathological assessment. Data were analyzed using mixed-effect models with backward timescales. Findings: Compared to participants who remained cognitively intact, olfactory identification declined faster among those who developed MCI (β −0.09 [95% CI −0.13, −0.05]), leading to a significantly lower olfactory identification starting from five years preceding MCI diagnosis (mean difference at year −5: −0.39 [−0.71, −0.07]). Among participants with incident MCI, olfactory identification declined faster in those who developed dementia compared to those who did not (β −0.19 [−0.36, −0.01]), leading to a significantly lower olfactory identification starting from three years preceding dementia diagnosis (mean difference at year −3: −0.95 [−1.67, −0.23]). A faster decline in olfactory identification was associated with higher burdens of global Alzheimer’s disease pathology, neurofibrillary tangles, and amyloid beta load. Interpretation: Olfactory identification declined faster preceding dementia disorders and Alzheimer’s pathology may underlie these faster declines. Funding: This study was funded by the National Institutes of Health (R01AG17917) and Swedish Research Council (2021-01647).